Evaluating the Sunk Cost Effect - David Ronayne; Daniel Sgroi; Anthony Tuckwell (Institute of Labor Economics (IZA), 2021)
We provide experimental evidence of behavior consistent with the sunk cost effect. Subjects who earned a lottery via a real-effort task were given an opportunity to switch to a dominant lottery; 23% chose to stick with their dominated lottery. The endowment effect accounts for roughly only one third of the effect. Subjects' capacity for cognitive reflection is a significant determinant of sunk cost behavior. We also find stocks of knowledge or experience (crystallized intelligence) predict sunk cost behavior, rather than algorithmic thinking (fluid intelligence) or the personality trait of openness. We construct and validate a scale, the "SCE-8", which encompasses many resources individuals can spend, and offers researchers an efficient way to measure susceptibility to the sunk cost effect.
Keywords: D91; C83; C90; 330; sunk cost effect; sunk cost fallacy; endowment effect; cognitive ability; fluid intelligence; crystallized intelligence; reflective thinking; randomized controlled trial; online experiment; online survey; psychological scales; scale validation; Raven's progressive matrices; international cognitive ability resource; cognitive reflection test; openness